Handwashing behavior and habit formation in the household: evidence from the pilot randomized evaluation of HOPE SOAP© in South Africa - Sellman, Abigail (School of Economics, 2019)
Handwashing with soap at critical times is a simple and effective way to prevent the spread of communicable diseases, such as diarrhea and acute respiratory infection, which are major causes of morbidity and mortality in developing countries. However, rates of handwashing remain low throughout the world, and interventions which attempt to improve handwashing behaviors have largely been unsuccessful in practice. This may be because behavior change programs often fail to recognize the habitual drivers of handwashing behavior. In contrast, this paper examines the effectiveness of a novel soap technology, HOPE SOAP©, a child-size and colorful bar of soap with a toy embedded in its center, which aims to increase handwashing in children by specifically targeting its habitual nature. To rigorously evaluate HOPE SOAP©, this paper exploits data from a pilot randomized controlled trial whereby 229 households from a poor urban community in South Africa were randomly assigned to receive HOPE SOAP© for a period of 12-weeks. In an initial analysis of the effects of the intervention on children’s health and behavior, Burns, Maughan-Brown, and Mouzinho (2017) found that that HOPE SOAP© had positive impacts on children’s handwashing behaviors and health outcomes. Children who received HOPE SOAP© children were more likely to wash their hands, and had better overall health outcomes than control children (Burns, Maughan-Brown, and Mouzinho 2017). Although HOPE SOAP© aims to induce behavior change in children, this paper explores the spillover effects that it has on other members of children’s households. Specifically, this work uses regression analysis to investigate the impacts of HOPE SOAP© on the handwashing behaviors of children’s primary caregivers, and on the health outcomes of all non-treated household members. This paper finds compelling evidence illustrating that a child’s assignment to HOPE SOAP© has a positive impact on the handwashing behavior of their caregiver. Specifically, HOPE SOAP© increases the probability that a caregiver will wash their hands before eating a snack by 13 percentage points on average (p-value 0.17). A further investigation of the causal mechanisms for this improvement suggests that HOPE SOAP© affects caregiver behavior both by disrupting existing poor-hygiene habits, and by strengthening handwashing norms within households. Despite its positive effects on household handwashing behavior, this paper finds that a child’s assignment to HOPE SOAP© has no discernable shortterm impacts on the health of individual household members. Nevertheless, the positive influence of HOPE SOAP© on caregiver handwashing behavior is promising and, in conjunction with the finding that HOPE SOAP© improves children’s behaviors, provides reason to believe the intervention may be successful in inducing habitual handwashing behaviors which can persist in the long run.